Self-reported chronic back pain in the elderly living in rural riverine areas in the Amazon - Aline Queiroz; Jansen Estrázulas; Luiza Garnelo; Evelyne Mainbourg; Fernanda Fonseca; Fernando Herkrath (James Cook University, 2022)
Introduction: The present study aimed to estimate the prevalence of self-reported chronic low back pain and to identify the associated factors in elderly people living in rural riverside areas in the Amazon. Methods: Data from a cross-sectional home-based survey performed in 38 riverside rural locations along the left bank of the Negro River, in the municipality of Manaus, Amazonas, Brazil, were analyzed. The selected elderly people answered a questionnaire comprising items related to the living conditions, socioeconomic and demographic characteristics, health status and utilization of health services. The outcome was self-reported chronic back pain or problem. The association between the outcome and the independent variables was assessed using logistic regression, estimating the odds ratios and respective 95% confidence intervals (CIs). Results: One hundred and six residents aged 60 years or older out of a total of 277 were included in the study. The prevalence of chronic back pain among the elderly residents was 57.5% (63.3% among men and 50.0% among women). Most of them did not have any treatment related to their chronic condition (77.0%). Occupation in activities other than agricultural activities was protective for the outcome (odds ratio (OR)=0.1, 95%CI=0.0-0.9). The chronic low back pain was also associated with worse self-perceived health (OR=10.3, 95%CI=1.6-67.5). Conclusion: The high prevalence of chronic low back pain in elderly people living in rural riverside areas, along with limited access to treatment and the different impacts on the performance of daily activities and the quality of life, reveals the relevance of this condition as a public health problem.